Assessment of mobile taxi booking apps: An empirical study of adoption by taxi drivers in Medellín-Colombia (2020)
This paper aims to explore the variables that precede the intention and use of Mobile taxi booking (MTB) Apps as tools for taxi drivers to make contact with customers in the city of Medellin, Colombia. A literature review was carried out to select the variables that most effectively represent the analysed behaviour. The methodology was a quantitative study based on theories technology adoption such as the planned behaviour model, the model of the theory of technology adoption, and the unified theory of acceptance and use of technology. The data was collected in Medellin Colombia by means of surveying taxi drivers who use MTB Apps. The data analysis Partial Least Square (PLS) was used and the result more important is the evidence that taxi drivers take the positives factors that this technology provides to contact customers. © 2020 Elsevier Ltd